PREVALENCE OF HYPOMAGNESEMIA IN CIRRHOSIS OF LIVER AND ITS ASSOCIATION WITH SEVERITYOF THE DISEASE - G, VEENA; JAMES, REBECCA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study are as follows: (1) To study the prevalence of hypomagnesemia in liver cirrhosis patients. (2) To evaluate association between hypomagnesemia and severity of liver disease. Methods: It was a cross-sectional study for 1 year. Seventy-one liver cirrhosis patients attending medicine OPD and those admitted in ward, ICU at Government Medical College, Kozhikode. Informed consent was taken from 71 liver cirrhosis patients. Samples for serum magnesium, total bilirubin, and albumin were collected from cases in blood collection tube without anticoagulant and centrifuged to get serum. Estimation of magnesium was done using colorimetric end point method. Estimation of total bilirubin was done using Diazo method and that of serum albumin with Bromocresol Green dye method. SPSS (Version 22.0) was used for analysis. Results: Among the study patients, hypomagnesemia was prevalent in majority (71.8%) of cases. The mean magnesium levels between different grades of liver cirrhosis were statistically significant at p=0.001. Levels of serum magnesium were significantly decreased with advancement of liver cirrhosis. Conclusion: Hypomagnesemia is prevalent in liver cirrhosis patients. Serum magnesium decreases significantly with severity of liver cirrhosis. A routine assessment of serummagnesium in liver cirrhosis patients may be effective in management protocol ofliver cirrhosis.